ORGANIZATION FEATURES ANALYSIS OF MODERN HELICOPTER EQUIPMENT PRODUCTION - Maria Vladimirovna Kolgan (Advanced Engineering Research)
The current status of the helicopter engineering in Russia is considered, the development prospects of the industry are evaluated. In the given period, the capital assets consolidation, and big business creation are being completed. Their manufacturing programs are aimed at the priority directions of the Russian aircraft industry. The significance of the chosen theme is caused by the role which the helicopter industry plays in forming scientific and economic potential of the country. At the present stage of the Russian economy development, problems on the organizational arrangement, divercification, entry into new markets become more urgent for helicopter equipment producers. In this regard, the focal points of the efficient manufacturing process control are considered by the example of the “Russian Helicopters” company. The following figures are analyzed: the Russian and world market shares of the “Russian Helicopters” company, operations efficiency improvement, development of new trends which will become additional sources of revenue.